Ultrasonografical monitoring as diagnostic tool for reproductive management in female buffaloes (bubalus bubalis) - Calogero STELLETTA; Koray TEKİN; Beste ÇİL; Fatma ÖZTUTAR STELLETTA; Ali DAŞKIN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2018)
The aim of this study was to estimate the frequency of physiological and pathological reproductive conditions in female Italian Mediterranean Buffaloes. Female animals (n=444), ranging from 3 to 14 years of age were monitored by ultrasonography (USG). A total of 7319 USG images were collected and analyzed for pregnancy status, fetal sexing, gynecological measurements and pathologies. While pregnancy rate was determined as 38.75% and ovarium-genital canal disorders as 11.71%; the most common pathologies in nonpregnant animals are defined as ovarian cystic degeneration (OCD), hydrosalpinx and salpingitis (SALP), metritis, pyometra (METR) and pneumovagina (PVAG). OCD represented 4.27% of pathological conditions during long day season (February-June) with a higher frequency above 5 years of age (P<0.05); and characterized by the presence of rounded anechoic structures with a 3.12±0.54 cm outer and 2.5±0.22 cm an internal diameter. While SALP frequency was determined as 6.75% and more intense over 7 years; METR and PVAG frequencies were 0.67% in total. In conclusion, these results demonstrated that ultrasonographic monitoring is a useful diagnostic tool to optimize the reproductive management through pregnancy and delivery time determination in addition to certain pathological conditions of the reproductive tract in buffaloes.